Effects of an immunomodulatory feed additive on body weight, production parameters, blood metabolites, and health in multiparous transition Holstein cows. (21st December 2018) - Wu, Zhaohai; Alugongo, Gibson M.; Xiao, Jianxin; Li, Jinghui; Yu, Yan; Li, Yuanxiao; Wang, Yajing; Li, Shengli; Cao, Zhijun
Abstract: The study investigated the impact of feeding OmniGen‐AF ® (OG; Phibro Animal Health, Quincy, IL) from dry‐off to week 4 of lactation at two doses on production performance and metabolic adaptation of multiparous Holstein cows. Forty‐eight cows were blocked and assigned randomly to three treatments: OG was fed at 0 g/head/day (CON), 60 g/head/day (OG60), or 90 g/head/day (OG90). No difference was observed in dry matter intake (DMI) throughout the experiment, whereas feeding OG tended to decrease the percentage body weight change (PWC) on week 2. Although colostrum yield was not affected by treatment, colostrum IgG production of OG90 tended to be higher than that of CON. OG supplementation did not affect overall milking performance but decreased milk SCC during the first 4 weeks of lactation. In prepartum, OG supplementation decreased the concentrations of serum albumin and calcium, and increased serum globulin. OG supplementation tended to increase serum total protein, globulin, and calcium contents postpartum. Furthermore, reduced incidence of mastitis and udder edema were observed. In conclusion, supplementing cows with OG from dry‐off period reduces or modulates the inflammation responses associated with parturition, potentially resulting in improved postpartum health, while feeding OG more than 60 g/head/day did not warrant further benefits.